Longitudinal Effects of Early Reading Interventions on Normed, Standardized Reading Outcome Measures. - Carroll, Deborah A. (2019)
Keywords: dept.psy; faculty_collection; sabbatical_report

Screening for reading disability in university students with phonological processing and working memory tasks - Broggi, M., Jr.; Ready, R.E.; Moore, D.L. (Dyslexia, 2019)
Many students in higher education have undiagnosed reading disabilities (RDs), but there are few measures to screen for RD in this population. The aim of this study was to determine the ability of tasks that are sensitive to RDs—such as measures of phonemic awareness and working memory—to differentiate university students previously diagnosed with RDs from controls. Participants were university students with an RD (n = 26), a clinical control group diagnosed with attention-deficit/hyperactivity disorder (n = 24), and neurotypical controls (n = 44). Participants completed brief phonological processing and working memory tasks. The RD group scored significantly lower on all tasks than both control groups. The phonological processing tasks alone—without the working memory task—discriminated participants with RDs from controls with excellent sensitivity and specificity. A brief battery of phonemic tasks could be an effective screening instrument for persons with RDs on university campuses. © 2019 John Wiley & Sons, Ltd.
Keywords: Attention Deficit Disorder with Hyperactivity; Awareness; Dyslexia; Female; Humans; Learning Disorders; Male; Memory, Short-Term; Phonetics; Reading; Students; Task Performance and Analysis; Universities; Young Adult; attention deficit disorder; awareness; dept.psy; dyslexia; female; human; learning disorder; male; peer-reviewed; phonetics; phonological processing; psychology; reading; reading disability; screening test; short term memory; student; task performance; university; university students; working memory; young adult

Experimentally induced variation in neuroendocrine processes affects male reproductive behaviour, sperm characteristics and social interactions - Nugent, Bridget M.; Stiver, Kelly A.; Hofmann, Hans A.; Alonzo, Suzanne H. (Molecular Ecology, 2019)
While extensive research has focused on how social interactions evolve, the fitness consequences of the neuroendocrine mechanisms underlying these interactions have rarely been documented, especially in the wild. Here, we measure how the neuroendocrine mechanisms underlying male behaviour affect mating success and sperm competition in the ocellated wrasse (Symphodus ocellatus). In this species, males exhibit three alternative reproductive types. “Nesting males” provide parental care, defend territories and form cooperative associations with unrelated “satellites,” who cheat by sneaking fertilizations but help by reducing sperm competition from “sneakers” who do not cooperate or provide care. To measure the fitness consequences of the mechanisms underlying these social interactions, we used “phenotypic engineering” that involved administering an androgen receptor antagonist (flutamide) to wild, free-living fish. Nesting males treated with flutamide shifted their aggression from sneakers to satellite males and experienced decreased submissiveness by sneaker males (which correlated with decreased nesting male mating success). The preoptic area (POA), a region controlling male reproductive behaviours, exhibited dramatic down-regulation of androgen receptor (AR) and vasotocin 1a receptor (V1aR) mRNA following experimental manipulation of androgen signalling. We did not find a direct effect of the manipulation on male mating success, paternity or larval production. However, variation in neuroendocrine mechanisms generated by the experimental manipulation was significantly correlated with changes in behaviour and mating success: V1aR expression was negatively correlated with satellite-directed aggression, and expression of its ligand arginine vasotocin (AVT) was positively correlated with courtship and mating success, thus revealing the potential for sexual selection on these mechanisms. © 2018 John Wiley & Sons Ltd
Keywords: 11-ketotestosterone; Androgen Receptor Antagonists; Animals; Brain; Female; Flutamide; Male; Neurosecretory Systems; Perciformes; RNA, Messenger; Receptors, Androgen; Reproduction; Sexual Behavior, Animal; Social Behavior; Spermatozoa; Testosterone; alternative reproductive tactics; androgen receptor; androgen receptor antagonist; androgens; animal; brain; dept.psy; drug effect; female; flutamide; genetics; male; messenger RNA; metabolism; neuroendocrine; neuroendocrine system; peer-reviewed; physiology; reproduction; sexual behavior; sexual selection; social behavior; social behaviour; spermatozoon; teleosts; testosterone

Neuropeptide manipulation has behavioural and cascading fitness consequences in wild-living fish - Stiver, Kelly A.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H. (Animal Behaviour, 2019)
Due to the difficulty of simultaneously assessing variation in individual physiology, behaviour and fitness, we often know little about the mechanistic basis of life-history trade-offs and fitness variation. It is similarly challenging to examine how physiological variation in one individual has cascading fitness consequences for others in the social environment. Using a wild-living fish (ocellated wrasse, Symphodus ocellatus), we manipulated a neuropeptide pathway associated with courtship, aggression and parental care in vertebrates (arginine vasotocin, AVT) and directly examined the behavioural and fitness consequences. Nesting males injected with the AVT antagonist increased their paternal care, resulting in increased hatching of offspring and increased reproductive success of all individuals that mated at his nest. By directly examining physiology, behaviour and reproductive success, we revealed how a small change in individual physiology has clear and direct fitness consequences for multiple individuals. © 2019 The Association for the Study of Animal Behaviour
Keywords: Symphodus ocellatus; Vertebrata; arginine vasotocin; behavioral response; dept.psy; fitness; fitness consequences; life history; nonapeptide; parental care; parental investment; paternal care; peer-reviewed; peptide; phenotype; phenotypic engineering; physiological manipulation; physiology; proximate mechanisms; reproductive cost; reproductive investment; reproductive success; trade-off; trade-offs; wild population

The efficacy of free-recall, cognitive load, and closed-ended questions when children are asked to falsely testify about a crime - Wyman, Joshua; Foster, Ida; Crossman, Angela; Colwell, Kevin; Talwar, Victoria (Applied Cognitive Psychology, 2019)
The current study evaluated the benefits of free-recall, cognitive load, and closed-ended questions on children's (ages 6 to 11; N = 147) true and false eyewitness disclosures. Children witnessed an experimenter find a stranger's wallet and were then asked to make a false denial, false accusation, true denial, or true accusation regarding an alleged theft. Overall, the free-recall question resulted in longer, more forthcoming and more detailed disclosures from older children and those who made a truthful accusation; however, children under the age of 9 and lie-tellers mostly relied on the closed-ended questions to discuss the theft. Although the cognitive load questions resulted in newly recalled information, there were no significant narrative differences between true and false statements on these questions. These findings suggest that forensic professionals should consider a child's developmental level, statement veracity, and disclosure-type (denial vs. accusation) when examining the efficacy of these commonly used questioning strategies.
Keywords: article; child; children; cognitive load; dept.psy; drug efficacy; eyewitness reports; false reports; female; free-recall; human; human experiment; major clinical study; male; narrative; peer-reviewed; recall; theft; witness

The language of wisdom understood through an analysis of wise quotes - DeFrank, Melanie; Bivona, Marissa; Chiaraluce, Brianna; Kahlbaugh, Patricia (Journal of Language and Social Psychology, 2019)
Wise quotes carry advice about how to navigate life's difficult decisions or feelings, allowing cultures to pass wisdom through generations. Qualities of wisdom have been identified by careful examination of wise individuals. Similarly, wise sayings and quotations can be analyzed and interpreted as emblematic of cultural beliefs about wisdom. The present research examines thematic and linguistic qualities of 157 wise quotes nominated as wise by 194 undergraduates. Thematic analysis of wise quotes centered on five dimensions of wisdom: Humor, Emotion, Review, Openness and Experience. Humor and Emotion were found to be the least represented while Review and Experience were the most represented. Linguistic analysis compared strong (n = 101) versus weak (n = 56) wise quotes and found that strong wise quotes were more linguistically complex and less likely to use the first-person pronouns. Analyzing the language of wisdom through quotes can provide additional insight into cultural representations of wisdom.
Keywords: adult; article; communicating wisdom; controlled study; dept.psy; female; human; human experiment; humor; language; major clinical study; male; peer-reviewed; quotes; text analysis; thematic analysis; wisdom

Tests of an indifference rule in variable-delay and double-reward choice procedures with humans - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2019)
Four hundred and fifty participants were recruited from Amazon Mechanical Turk across 3 experiments to test the predictions of a hyperbolic discounting equation in accounting for human choices involving variable delays or multiple rewards (Mazur, 1984, 1986). In Experiment 1, participants made hypothetical choices between 2 monetary alternatives, 1 consisting of a fixed delay and another consisting of 2 delays of equal probability (i.e., a variable-delay procedure). In Experiment 2, participants made hypothetical monetary choices between a single, immediate reward and 2 rewards, 1 immediate and 1 delayed (i.e., a double-reward procedure). Experiment 3 also used a double-reward procedure, but with 2 delayed rewards. Participants in all 3 experiments also completed a standard delay-discounting task. Finally, 3 reward amounts were tested in each type of task ($100, $1000, and $5000). In the double-reward conditions (Experiments 2 and 3), the results were in good qualitative and quantitative agreement with Mazur's model (1984, 1986). In contrast, when participants made choices involving variable delays (Experiment 1), there was relatively poor qualitative and quantitative agreement with this model. These results, along with our previous findings, suggest the structure of questions in hypothetical tasks with humans can be a strong determinant of the choice pattern.
Keywords: Adult; Choice Behavior; Delay Discounting; Female; Humans; Male; Models, Psychological; Probability; Reward; adult; choice; decision making; delay discounting; dept.psy; female; human; humans; hyperbolic discounting; male; mathematical model; peer-reviewed; probability; psychological model; reward

Using the reality interview improves the accuracy of the Criteria‐Based content analysis and reality monitoring - Bogaard, Glynis; Colwell, Kevin; Crans, Samantha (Applied Cognitive Psychology, 2019)
Active interviewing approaches can exploit the verbal differences between truthtellers and liars, thus improving detecting deception. One such method is the Reality Interview (RI) aimed to facilitate recall from truthtellers, while increasing the difficulty for liars. This study investigated whether the RI could improve the diagnostic accuracy of the Reality Monitoring and the Criteria-Based Content Analysis. Liars and truthtellers were either asked to freely recall an event or interviewed with the RI. As hypothesized, the RI improved the discriminability of Reality Monitoring and Criteria-Based Content Analysis over Free Recall. Honest responses were longer, and the RI increased the word count difference between honest and false statements. However, after correcting for word count, results were no longer significant, showing its importance for deception detection. Nonetheless, the RI increased verbal differences between truthtellers and liars, demonstrating that using the RI with verbal credibility assessment tools is a powerful combination for investigative interviewing. © 2019 The Authors Applied Cognitive Psychology Published by John Wiley & Sons Ltd.
Keywords: Criteria-Based Content Analysis; Reality Interview; Reality Monitoring; article; content analysis; credibility assessment; deception; deception detection; dept.psy; diagnostic accuracy; diagnostic test accuracy study; human; human experiment; interview; monitoring; peer-reviewed; recall

Social anxiety and employment interviews: does nonverbal feedback differentially predict cortisol and performance? - Budnick, Christopher J.; Anderson, Eden M.; Santuzzi, Alecia M.; Grippo, Angela J.; Matuszewich, Leslie (Anxiety Stress and Coping, 2019)
Background & Objectives: Interviewers often provide positive nonverbal feedback to reduce interviewees' anxiety. Socially anxious individuals typically harbor negative self-views discrepant with positive feedback. We examined whether nonverbal feedback and social anxiety jointly influence cortisol responses to, and performance during, interviews. Design: An experimental between-subjects design randomly assigned participants to feedback condition. Methods: Undergraduate students (N = 130) provided saliva and completed social anxiety, interview anxiety, and affective measures before a simulated interview. Following a standardized script, a confederate interviewer provided positive, ambiguous, or negative nonverbal feedback. Participants then provided saliva and completed self-focused attention and self-awareness measures. Confederate interviewers and an external rater evaluated participants' anxiety displays, assertive behavior, and performance. Results: Positive feedback decreased cortisol and improved performance for low social anxiety participants. Socially anxious participants exhibited higher cortisol but did not exhibit significant differences in performance after positive compared to negative feedback. Conclusions: Consistent with previous findings, positive feedback did not benefit socially anxious interviewees. Positive feedback increased physiological arousal relative to negative feedback but did not hinder performance among people high in social anxiety. These results provide novel information about the interactive influence of social anxiety and nonverbal interviewer feedback on arousal, self-focus, and interview performance.
Keywords: Anxiety; Arousal; Attention; Feedback; Female; Humans; Hydrocortisone; Interviews as Topic; Job Application; Male; Saliva; Social anxiety; anxiety; arousal; attention; chemistry; controlled study; cortisol; dept.psy; feedback system; female; human; hydrocortisone; interview; interview anxiety; interviews; job finding; male; pathophysiology; peer-reviewed; psychology; randomized controlled trial; saliva; self-verification

Restraint stress exacerbates cell degeneration induced by acute binge ethanol in the adolescent, but not in the adult or middle-aged, brain - Fernandez, Macarena Soledad; de Olmos, Soledad; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2019)
Restraint stress (RS) induces neurotoxicity in the hippocampus, yet most of the studies have employed protracted RS (i.e., = 21 days). Binge ethanol can induce brain toxicity, an effect affected by age. It could be postulated that RS may facilitate ethanol-induced neurotoxicity, perhaps to a greater extent in adolescent vs. older subjects. We analyzed whether adolescent, adult or middle-aged male rats exposed to five episodes of RS followed, 72h later, by binge ethanol (i.e., two administrations of 2.5 g/kg ethanol) exhibited hippocampal neurotoxicity. Adolescents, but not adult or middle-aged rats, exhibited sensitivity to the neurotoxic effects of ethanol at dorsal CA2, ventral CA3 and ventral DG, and a neurotoxic effect of stress at dorsal CA1. Moreover, the combination of ethanol and stress exerted a synergistic effect upon cell degeneration at ventral CA1 and CA2, which was restricted to adolescents. Ethanol also increased cell degeneration, irrespective of age or stress, in dorsal CA3 and in dorsal DG; and ethanol and stress had, across all ages, a synergistic effect upon cell degeneration at the dorsal CA1. The greater neurotoxic response of adolescents to ethanol, stress, or ethanol+stress can put them at risk for the development of alcohol problems. Copyright © 2019 Elsevier B.V. All rights reserved.
Keywords: *Age Factors; *Binge Drinking/pp [Physiopathology]; *Ethanol/ae [Adverse Effects]; Adolescent; Adult rats; Age Factors; Animals; Article; Binge Drinking; Binge Drinking/me [Metabolism]; Brain; Brain/de [Drug Effects]; Dentate Gyrus; Dentate Gyrus/de [Drug Effects]; Ethanol; Ethanol/pd [Pharmacology]; Hippocampus; Hippocampus/de [Drug Effects]; Male; Middle-Aged rats; Neurotoxicity; Rats; Rats, Wistar; Restraint, Physical; Wistar rat; adolescent; adult; adult animal; age; alcohol; animal; animal behavior; animal cell; animal experiment; animal model; animal tissue; binge drinking; brain; controlled study; dentate gyrus; dept.psy; dorsal hippocampus; drinking behavior; drug effect; exercise; hippocampal CA1 region; hippocampal CA2 region; hippocampal CA3 region; hippocampus; immobilization stress; male; metabolism; middle aged; nerve cell degeneration; neurotoxicity; nonhuman; pathophysiology; peer-reviewed; priority journal; rat; sensitivity analysis; underage drinking; ventral dentate gyrus; ventral hippocampus

Offspring of male rats exposed to binge alcohol exhibit heightened ethanol intake at infancy and alterations in T-maze performance. - Hollander, Jessica; McNivens, Megan; Pautassi, Ricardo M; Nizhnikov, Michael E (Alcohol, 2019)
Alcohol use is associated with a variety of negative consequences, including heightened likelihood of cognitive impairment, proclivity to alcohol use disorders (AUD), and alterations in the drinker's offspring. Children and rodents exposed to alcohol during pregnancy, or those whose fathers consumed alcohol prior to mating, often exhibit neurodevelopmental, physiological, and behavioral deficits. The present study assessed cognitive function and alcohol intake in male and female rats that were offspring of alcohol-exposed fathers. Adult male rats were exposed to alcohol or vehicle (0.0 or 2.0 g/kg, respectively; twice daily for 2 days followed by a rest day, for a total of eight alcohol or vehicle exposure days), or were left untreated and then mated with non-manipulated females. The offspring were assessed for alcohol intake, via intraoral infusion, followed by cognitive assessment via an alternating T-maze task. The results indicated that paternal ethanol exposure, prior to breeding, resulted in offspring that consumed significantly more ethanol than vehicle or untreated controls. Furthermore, the offspring of alcohol-exposed fathers exhibited a significant failure to initiate and complete the T-maze performance tests. Although, when they did engage in the tests they performed at the level of controls (i.e., 80% correct). The present results add to a growing body of literature suggesting that paternal pre-conception alcohol exposure can have deleterious effects on the offspring. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/px [Psychology]; *Binge Drinking/px [Psychology]; *Fathers/px [Psychology]; *Maze Learning/de [Drug Effects]; *Prenatal Exposure Delayed Effects/px [Psychology]; Alcohol Drinking; Alcohol intake; Animals; Article; Binge Drinking; Fathers; Female; Male; Maze Learning; Paternal alcohol exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; T-maze; T-maze test; adult; alcohol; alcohol consumption; animal; animal experiment; binge drinking; cognition; controlled study; dept.psy; drinking behavior; drug effect; father; female; male; maze test; nonhuman; paternal exposure; peer-reviewed; pregnancy; prenatal exposure; psychology; rat

Language choice matters: when profanity affects how people are judged - DeFrank, Melanie; Kahlbaugh, Patricia E (Journal of Language and Social Psychology, 2019)
Swearing is prevalent in our society, but the influence of such language choices on judgments of others is not well understood. This study examines how the composition of conversational dyads, speaker's gender, and use of profanity influence impressions. Participants (N = 138) were randomly assigned to read two conversations and rate target speakers (one male, one female). The conversations had neither, one, or both speakers using profanity and consisted of same- or mixed-gender dyads. The result is a 2 (target speaker, male/female) x 2 (dyad composition) x 3 (profanity) mixed design with speaker gender as the repeated measure. Speakers using profanity had poorer impression ratings on several variables, including overall impression, intelligence, and trustworthiness. Speakers swearing in mixed-gender dyads were rated as less sociable, and males swearing in mixed-gender dyads were rated as more offensive. Language choices matter, and more research is needed to understand the unconscious biases held against those who use profanity.
Keywords: adult; article; controlled study; conversation; dept.psy; ego development; female; gender; human; human experiment; impression formation; intelligence; language; major clinical study; male; peer-reviewed; profanity; randomized controlled trial

A comparison of different investigative interviewing techniques in generating differential recall enhancement and detecting deception - De Rosa, Jacob; Hiscockanisman, Cheryl; Blythe, Adam; Bogaard, Glynis; Hally, Ashley; Colwell, Kevin (Journal of Investigative Psychology and Offender Profiling, 2019)
This study compared the Stepwise Interview, Cognitive Interview, and Reality Interview in detecting deception with inmates. The dependent measures were the amount of unique details provided during the free narrative and mnemonics and the number of words provided during the free narrative and mnemonics of each interview. The Stepwise Interview generated 58.3% accuracy, the Cognitive Interview generated 70.0% accuracy, and the Reality Interview generated 93.3% accuracy. The different tasks of these interviews increased the differences between honest and deceptive statements and therefore, increased the accuracy in detection of deception. Differential recall enhancement is used to explain the findings.
Keywords: credibility assessment; dept.psy; detecting deception; investigative interviewing; peer-reviewed

Does eyewitness and interviewer gender influence children’s reports? An experimental analysis of eyewitness and interviewer gender on children’s testimony - Foster, Ida; Wyman, Joshua; Tong, Donia; Colwell, Kevin; Talwar, Victoria (Psychiatry, Psychology and Law, 2019)
This study examines how children's age, gender and interviewer gender affected children's testimony after witnessing a theft. Children (N=127, age = 6-11 years) witnessed an experimenter (E1) find money, which he/she may/may not have taken. E1 then asked the children to falsely deny that the theft occurred, falsely accuse E1 of taking the money, or tell the truth when interviewed by a second experimenter. Falsely denying or falsely accusing influenced children's forthcomingness and quality of their testimony. When accusing, boys were significantly more willing than girls to disclose about the theft earlier and without being asked directly. When truthfully accusing, children gave lengthier testimony to same-gendered adults. When denying, children were significantly more willing to disclose the theft earlier to male interviewers than to females. As children aged, they were significantly less likely to lie, more likely to disclose earlier when accusing, and give lengthier and more consistent testimony.
Keywords: adult; article; child; children; dept.psy; disclosures; false accusations; false denials; female; gender; girl; human; interviewer gender; lying; major clinical study; male; money; peer-reviewed; preschool child; theft; witness

Audiovisual speech perception in children with autism spectrum disorders - Irwin, Julia R.; Avery, T; Kleinman, D; Landi, N (ICA 2019 Aachen, 2019)
In face-to-face conversation, when a speaker talks, the outcome of their speech can both be heard (audio) and seen (visual). We employed a novel visual phonemic restoration paradigm to assess neural signatures (event related potentials [ERPs]) of audiovisual processing in typically developing children and in children with ASD. During EEG recording, two types of auditory stimuli were alternately presented with video of a speaker saying the consonant-vowel syllable /ba/: 1) a synthesized consonant-vowel syllable /ba/ or 2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant are substantially weakened, such that it sounds more like /a/. The auditory stimuli are easily discriminable, however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. In an ERP context, we have shown that this restoration leads to an attenuated phoneme discrimination response in an active task in typical adults and children. To explore the hypothesis that children with autism spectrum disorder (ASD) have atypical AV speech integration under pre-attentive processing conditions, we tested whether children with ASD would show a reduction in this restoration effect under passive listening conditions. Indeed, in this task, children with ASD showed a large /ba/-/a/ discrimination response, even in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2019 Proceedings of the International Congress on Acoustics. All rights reserved.
Keywords: Audiovisual; Autism; Phonemic Restoration; Speech; dept.psy